Empowering Students Through Increasing Santriprenuer Knowledge - Fuady, Muhammad Noor; Ramadan, Willy; Nurani, Muhammad Fahmi; Pranajaya, Syatria Adymas (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Islamic boarding schools are required to be agents of development, playing an active role in contributing to and transforming the field of economic empowerment and the quality of their resources. Many Islamic boarding schools have adapted and transformed into institutions that participate in economic empowerment efforts, but the programme only involves motivators and target groups without the involvement of the students, both cognitively and in terms of action. Thus, students must be empowered. Among the skills that students should be prepared with are those that will enable them to support the pesantren's economy and also add value for them when they return to society. The objective of this assistance is to enhance the understanding and awareness of students and pesantren on the significance of the creative industry for the advancement of pesantren and as a precursor for students after graduating from these educational institutions. Therefore, the research team/servant and the pesantren together explore the potential or assets that they have, develop appropriate programmes, and also evaluate the implemented programmes. The ABCD approach is a service methodology employed in this mentoring programme. This service technique is broadly divided into five stages: (1) Identification of community strengths; (2) Asset mapping of the community, (3) Planning the form of the mentoring programme; (4) programme implementation; (5) monitoring and evaluation (M&E) is conducted using the Most Significant Change (MSC) technique.